Популяризація краєзнавчої літератури музейними закладами Волинської губернії кінця ХІХ – початку ХХ століть - Кушпетюк, О. (Краєзнавство, 2019)
У статті аналізується діяльність працівників музейних закладів Волинської губернії кінця ХІХ –
початку ХХ століть щодо висвітлення історії краю шляхом публікації волинознавчих праць, підготовлених на основі зібраних і збережених ними ж музейних збірок. Зазначено, що публікації таких досліджень давали змогу музейним закладам широко заявити про себе і свою діяльність, сприяли пробудженню зацікавленості волинськими історією та пам'ятками та зростанню потягу до вивчення їх
минувшини, активізації історико-краєзнавчих досліджень загалом. The article analyses the activity of museum specialists of Volyn governorate in the end of the 19th-the beginning
of the 20th centuries to illuminate the history of the region by publishing Volyn science works on the
basis of gathered and preserved museum collections.
It was pointed out that the activities of the first Volyn museums were intended not only at the identification
and collection of local monuments, their processing and presentation in the exhibitions and maintaining their
proper storage. Considerable attention was paid to the study of antiquities, their popularization by publishing
Volyn science works on the basis of processed sights.
The authors of these Volyn science researches were participants of the museum construction of the region.
In the works of O.Dvernytskyi, O.Fotynskyi, F.Shteinhel, M.Trypolskyi, Ya.Yarotskyi and other researchers, a
range of issues of the history of Ukraine is considered, the process of proliferating of Volyn museums and the
beginning of their activity are described. The scholars emphasize the importance of studying of Volyn antiquities
which make it possible to highlight the past much broader and more thorough. The discovery, processing and
preservation of monuments with the help of museums plays an important teaching and educational role.
Publications of Volyn science works of the participants of the museum building enchanced the growing
interest on Volyn history and monuments, on the study of their past and the intensification of historical researches
in general.